2017
DOI: 10.24167/celt.v16i2.583
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Gender, Subject Preference and Learning Styles

Abstract: Abstract:Understanding the learning styles of the students is very crucial in implementing student-centered learning (SCL). The objectives of this research are to describe: 1) the general learning styles profile of the students of English Education Department, Muria Kudus University; 2) the dependency relationship between learning styles dimensions and gender, and 3) the dependency relationship between subject preference and learning styles dimensions. The participants of this research were 208 students from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…We found out that there was no statistically significant difference in learning styles between male and female students (p-value = 0.635). Our result has similar result with recent study by Yemane et al [17] and Gunes [18] which are also found that there was no significant difference in learning style preferences between the two gender. As comparison, learning styles differences also not found in other major such as in linguistic students [20,21,22].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found out that there was no statistically significant difference in learning styles between male and female students (p-value = 0.635). Our result has similar result with recent study by Yemane et al [17] and Gunes [18] which are also found that there was no significant difference in learning style preferences between the two gender. As comparison, learning styles differences also not found in other major such as in linguistic students [20,21,22].…”
Section: Discussionsupporting
confidence: 92%
“…A number of studies have shown a relationship between gender and learning style preferences of the students. Since the past few years, there has been a renewed interest in studies related to gender differences among students in higher schools in both in the world and Indonesia [15,16,17,18].However, this issue has been debated many times in the literatures is whether gender difference may affect an individual's preferences in learning [17,22]. Therefore, study about gender difference in learning styles also became our concern in this study.…”
mentioning
confidence: 99%
“…Furthermore, the farthest distance is used by male-male stranger within social level (3.7 m), whereas the closest distance is used by female-female non-strangers in distance less than 0.46 m. In addition, as seen in the figure 4, female-female nonstranger interaction also applies physical contact that is hand-holding. As Suprihadi & Rokhayani (2016) and Pasaribu & Kadarisman (2016) add that there is a difference in male and female in learning as well as in interacting socially-verbally and non-verbally.…”
Section: Figure 8: Proximity Between Female-female Non-strangersmentioning
confidence: 99%